(3GOGQI GdeSJTajGJ hGdQYGjI GdUMjI (B/s - (3RgQGf, eVQs ((3YeGf(B: s (3OGQ RgQGf ddfTQ hGdJhRjY(B, s, 2006)
(3GOGQI GdeSJTajGJ (B, (3GdegGQGJ GdGOGQjI(B, (3efGWb GdNOeGJ GdeJNUUI NOeGJ GdWhGQF GVGaI Gdi GdehGQO GdHTQjI h GOGQJgG h GNjQG GdeGdjI(B.s
Keywords: (3GOGQI GdeSJTajGJs; (3GdQYGjI GdUMjIs